Antibacterial effect of different concentrations of sodium hypochlorite on Enterococcus faecalis biofilms in root canals - Forough Reyhani, Mohammad; Rezagholizadeh, Yousef; Narimani, Mohammad Reza; Rezagholizadeh, Lotfollah; Mazani, Mohammad; Barhaghi, Mohammad Hossein Soroush; Mahmoodzadeh, Yavar (Journal of dental research, dental clinics, dental prospects, 2017)
The aim of this study was to evaluate the effectiveness of different concentrations of sodium hypochlorite (NaOCl) solution in reducing bacterial growth in Enterococcus faecalis biofilms in root canals. The root canals of maxillary central incisors of 104 subjects underwent chemomechanical debridement. In order to remove the smear layer, 5.25% sodium hypochlorite solution was used for 3 minutes in the root canals. Then, the samples were immersed in 1 mL of 17% EDTA for 3 minutes. Finally, the root canals were irrigated with phosphate-buffered saline (PBS) solution. After removing the smear layer, the samples were sterilized. Then E. faecalis biofilms formed within the root canals at 4-, 6-, and 10-week intervals were evaluated. Each group was divided into 4 subgroups in terms of the antibacterial treatment: group 1: 1% NaOCl solution; group 2: 2.5% NaOCl solution; group 3: 5.25% NaOCl solution; and group 4: PBS solution. After preparation of root canal filings, the counts of live bacteria were calculated through the classic method of counting, i.e. colony forming units (CFU), followed by the analysis of data. In groups 2 and 3, there was no bacterial growth due to complete removal of E. faecalis biofilms (P<0001), while the bacterial counts in group 1 at 4-, 6- and 10-week intervals decreased compared to the control group. The bacterial cells in mature and old biofilms have higher resistance to 1% NaOCl solution compared to the young biofilms. However, the 2.5% and 5.25% NaOCl solutions caused complete inhibition of the growth of E. faecalis biofilm in all the stages of development.